Fetal umbilical vein aneurysm - Samuel, Raisa; Navneetham, Preethi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Fetal umbilical vein aneurysm is an uncommon anomaly also known as umbilical vein varix. It accounts for 4% of umbilical cord abnormalities with an incidence of 0.4-1.1/1000. The etiology of fetal vein aneurysm has not been well established. The diagnosis is made by colour doppler sonography. The management of umbilical vein aneurysm is yet in process of establishment. The possibility of sudden hemodynamic change caused by aneurysm or thrombosis needs to be screened on a regular basis and early delivery can be considered in need.